Pengaruh Media Etnomatematika Permainan Engklek terhadap Kemampuan Pemecahan Masalah Bangun Datar Kelas III SB Kepong, Malaysia: The Influence of the Ethnomathematics Media of the Engklek Game on the Problem-Solving Ability of Flat Figures for Class III SB Kepong, Malaysia - Dwi Saidah Putri; Suci Perwita Sari (ITScience (Information Technology and Science), 2025)
This study aims to determine the effect of ethnomathematics media, in the form of engklek games, on the problem-solving abilities of third-grade students at SD Negeri Kepong, Malaysia. This is quantitative research. Mathematics learning in elementary schools generally still focuses on conventional methods that emphasize memorizing formulas for students without linking them to the context of students' lives. This condition affects low mathematical problem-solving abilities, especially with flat shapes. The ethnomathematics approach through the traditional game of engklek offers an alternative, contextual, and fun learning experience by linking local cultural elements to geometric concepts. This study used a pre-experimental, one-group pretest-posttest design with 6 third-grade students from SD Sanggar Bimbingan Kepong, Malaysia, selected using a total sampling technique. Data collection for this study was conducted as a pretest-posttest with 10 questions. Students were given a pretest before treatment, and then a posttest. The study found that ethnomathematics media in the form of engklek games, as a mathematics learning medium, influenced the learning outcomes of third-grade students at SD Negeri Kepong, Malaysia. This is evidenced by the change in the number of students who completed the learning, with an increase from the pretest (38.33) to the posttest (81.67). The normality test showed that the data were normally distributed (p> 0.05; pretest sig. value = 0.421; posttest sig. value = 0.212). The paired-samples T-test showed a significant result (p=0.000 <). Thus, the use of ethnomathematics media in the form of hopscotch games is effective in improving the ability to solve problems involving flat shapes and in making learning more active, fun, and meaningful.